Pengalaman Spiritual menurut Psikologi Transpersonal (Kajian Kritis Ilmu Tasawuf) - Ryandi Ryandi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
This study attempts to critically explore Transpersonal Psychology views on the nature of spiritual experience. The exponents of this kind of psychology claimed their concept as an integration between science and religion as well as it was can be universally accepted by all religions. Since this study reveals religious issues especially religious experience that in Islam is often said to be a sufi experience, then the approach of this study is sufism. From this study we found that the Transpersonal Psychology view is really problematic both epistemologically and theologically. Epistemologically, their assumptions are a priory i.e. they are not purely and intensely resulted by scientific research, but based on the premise of perennial philosophy which recognizes the transcendent unity of religions. Theologically, their assumptions lead to the refutation of religious doctrine. It yields a contemplative spiritual practice that ignores religious teaching. As a result, the spiritual knowledge is more subjective i.e. based on human ego, which finally leads to spiritual narcissism. It is really different from the sufis, which base their spirituality on religion, and subjectively affirm their experience to syariah. Psychologically, the sufi who has reached a spiritual state, his soul was in an existential consciousness on the level of faqr, that is a feeling of indebtedness to Allah. It causes the totality of servitude to Allah, not narcissism.